Дослідження ефективності інноваційного способу замороження та дефростації плодоовочевої сировини - Паляничка, Надія Олександрівна; Ялпачик, Володимир Федорович; Прокопенко, Олена Павлівна; Palianychka, Nadiia; Yalpachyk, Volodymyr; Prokopenko, Olena (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У роботі наведено результати експериментального дослідження процесів заморожування й дефростації плодоовочевої сировини в умовах підвищеного тиску. Установлено, що під час заморожування напружений стан клітинної стінки характеризується виникненням розтягувальних напруг, величина яких змінюється за гіперболічною залежністю по всій поверхні. З метою зниження максимальних розтягувальних напружень обґрунтовано необхідність створення зовнішнього навантаження на циліндричну оболонку, величина якого повинна відповідати гідростатичному тиску всередині клітини. За результатами проведеної роботи визначено оптимальні значення тиску, за яких доцільно здійснювати процеси заморожування та подальшої дефростації. Отримані експериментальні дані засвідчують ефективність запропонованого способу й підтверджують обґрунтованість застосування процесів заморожування та дефростації в умовах підвищеного тиску. /// EN: Extending the shelf life of fruit and vegetable products remains an important scientific and practical task, particularly in ensuring their consumption from harvest to harvest and, in some cases, over even longer periods. Freezing is considered one of the most promising approaches to addressing this issue. However, the final product quality after freezing largely depends on a properly selected defrosting regime and the conditions under which thawing is carried out. This study presents the results of an experimental investigation of the freezing and defrosting of fruit and vegetable raw materials under elevated pressure. The application of pressure improves product quality by minimizing cellular damage, preserving gases dissolved in the cell sap, and facilitating the recovery of the turgor state of plant tissues after thawing. It was established that during freezing the stress state of the cell wall is characterized by tensile stresses, whose magnitude changes according to a hyperbolic relationship over the entire cell surface. To reduce the maximum tensile stresses, the necessity of applying an external load to the cylindrical shell was substantiated; its value should correspond to the hydrostatic pressure inside the cell. Optimal pressure values for freezing and subsequent defrosting were determined: eggplants – 0.03 MPa, corn – 0.045 MPa, peppers – 0.067 MPa, and grapes – 0.07 MPa. Experimental tests showed that samples processed under applied pressure clearly outperformed those treated by conventional methods in external quality indicators, confirming the feasibility of freezing and thawing under elevated-pressure conditions. In particular, pressure-treated samples retained a more intact surface, firmer texture, and better overall appearance after defrosting too.
Efficiency of an innovative freezing and defrosting method for fruits and vegetables
Keywords: заморожування; дефростація; гідростатичний тиск; напруга; осмотичний тиск; клітина; freezing; defrosting; hydrostatic pressure; tension; osmotic pressure; temperature; cell; fruit and vegetable products